Product Differentiation Strategy at Nhanas Donuts Pinrang in Facing Culinary Business Competition in the Millennial and Gen Z Era - Kurniawaty; Yusrianti; Damayanti Trisnasari; Yayuk Astuti (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the product differentiation strategy implemented by Nhanas Donuts Pinrang in facing culinary business competition in the millennial and Gen Z era. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Informants consisted of the owner, production and service employees, as well as millennial and Gen Z consumers. The results showed that the product differentiation strategy applied includes four main aspects: flavor innovation with contemporary variants (matcha cheese, red velvet crumble, cookies and cream), attractive and